Preserving Identity through Modernity: Dayah al-Aziziyah and Its Negotiations with Modernity in Aceh - Ismail Fahmi Arrauf Nasution; Miswari Miswari; Sabaruddin Sabaruddin (Universitas Negeri Jakarta, 2019)
This paper aims to analyze the dayah negotiations in Aceh in the face of modernity. On the one hand, the dayah needs to maintain identity by caring for the uniqueness of the system and methods of religious teaching in accordance with methods that have been taught from generation to generation. Text review determined by the dayah teacher (teungku) starting from the criteria of the dayah student (santri) and the system of evaluation and standardization of abilities. Dayah also takes care of identity by forming the personality of the santri through the development of independence of life in the dayah. The dayah system has succeeded in giving birth to a society that understands Islam in a deep, comprehensive and far-reaching understanding of religion. More importantly, dayah education alienates santri from radical thought patterns and makes them tolerant humans. The results of this study show that Dayah Al-Aziziyah who cared about modernity by not losing its identity successfully spread religious teachings well in Aceh. Negotiations with modernity also made Al-Aziziyah a little left with some of its educational principles such as delaying the big vision to make Islamic Higher Educatin (Sekolah Tinggi Agama Islam, STAI) Al-Aziziyah Samalanga exactly like the dayah manyang (higher dayah level) that had been popular in Aceh.